Dual-functional sensing properties of ZnFe2O4 nanoparticles for detection of the chloramphenicol antibiotic and sulphur dioxide gas - Nguyen Thanh Vinh (Sensors and Actuators A: Physical, 2021)
Zinc Ferrite (ZnFe2O4, ZFO) nanoparticles (NPs) as a multi-sensing material are successfully synthesised via a hydrothermal method and a following annealing treatment. The as-prepared ZFO-NPs were applied in electrochemical and mass-type sensors by depositing NPs directly on the screen-printed electrode (SPE) and the active electrode of a quartz crystal microbalance (QCM), respectively. The obtained results show the ZFO-NPs possessed excellent detection performance to sulphur dioxide (SO2) in the range of 2.5–20 ppm at room temperature. QCM sensor coated with ZFO-NPs showed a high response, good repeatability, as well as short-response time. Moreover, the modified-SPE with ZFO-NPs sensitively responded to chloramphenicol (CAP) of concentration range from 5 to 50 μM in phosphate buffer solution (PBS). The sensing mechanism of ZFO-NPs based sensors towards SO2 and CAP was also discussed. This study demonstrates that ZFO-NPs could be known as a potential sensor material capable of detecting SO2 gas and CAP quickly in both mass-type gas sensors and electrochemical sensors.